How Significant Are Training and Certification in Shaping Indonesian Migrant Workers’ Long-Term Careers? - Yunus Riansyah; Lela Nurlaela Wati; Rita Yuni Mulyanti (Inclusive Society and Sustainability Studies, 2025)
This study investigates the effectiveness of competency certification in supporting the career continuity of Indonesian Migrant Workers (IMWs) in host countries. Mandated by Law No. 18 of 2017, competency certification is a prerequisite for placement, on the assumption that it ensures the quality and competitiveness of Indonesian labor. However, many IMWs continue to experience repatriation due to perceived incompetence. This research employed a qualitative case study approach through in-depth interviews with eight informants, three informal-sector IMWs in Taiwan, and five officials from BP3MI/KP2MI across various regions, supplemented by a focus group discussion with two policy experts. Thematic analysis using NVivo 12 identified five key themes: (1) challenges of varying standards, costs, and limited access; (2) the need for international recognition; (3) the role of government and private actors in monitoring and support; (4) certification as a driver of competitiveness and employment opportunities; and (5) certification as a legal safeguard and instrument of quality standardization. The findings show that certification positively influences IMWs’ entry into the international labor market and enhances their confidence. However, its long-term impact remains limited due to the absence of global recognition, misalignment between training curricula and workplace demands, and weak post-placement support. These results align with the Theory of Attitude and Behavior and the Theory of Planned Behavior, indicating that training fosters positive attitudes and social norms, yet sustained professional behavior is hindered by low perceived behavioral control caused by structural barriers. The study recommends harmonizing certification standards with destination countries, improving the relevance of training curricula, and strengthening institutional support after placement. Ultimately, competency certification must be complemented by continuous learning systems to effectively enhance IMWs’ quality and career sustainability.